A matter of good taste: investigating preferences for in-house water treatment in peri-urban communities in Cambodia. (24th August 2015) - Jeuland, Marc; Orgill, Jennifer; Shaheed, Ameer; Revell, Geoff; Brown, Joe
Abstract: Low demand for safe water may partly result from a perceived distaste towards or the inconvenience of treatment methods. This paper analyzes preferences for water quality improvements in peri-urban Phnom Penh. The authors first analyze data from a discrete choice experiment in which respondents selected their preferred alternative from generic options varying in cost, taste acceptability, effectiveness against diarrhea and quantity of water treated. The choice patterns suggest that demand for water treatment is highly dependent on taste acceptability. The authors also use double-blinded taste tests to show that respondents are sensitive to one common taste in treated drinking water, that stemming from chlorine disinfection. While many compounds (natural and anthropogenic) may contribute to taste problems in drinking water, the lack of alignment between household preferences for taste and water safety may play a role in the low use of household water treatment methods in many settings.